Digital Transformation of Ethnomathematics: Preserving Culture Through Technology in Mathematics Education - Benidiktus Tanujaya; Zidni Naufal Fadhil; Lisnani Lisnani (Journal of Emerging Technologies in Ethnomathematics, 2025)
The integration of technology in education has revolutionized various disciplines, and mathematics education is no exception. This paper explores the digital transformation of ethnomathematics, a field that connects mathematical concepts with cultural practices, and how this intersection can be enhanced through the use of modern technological tools. By leveraging technology, the study aims to preserve and promote cultural heritage while simultaneously improving mathematical learning outcomes. Through the development of interactive digital tools, such as augmented reality (AR) and virtual reality (VR) applications, the paper demonstrates how indigenous knowledge systems and cultural representations can be seamlessly incorporated into mathematics curricula. The integration of these tools not only makes learning more engaging but also fosters a deeper connection between students and the cultural contexts in which mathematical ideas originate. Furthermore, the study highlights the significance of ethnomathematics in fostering cultural awareness and appreciation among students while encouraging critical thinking and problem-solving skills. The paper concludes by discussing the implications of this digital transformation in ethnomathematics for both educators and students, providing a pathway for the future of culturally relevant mathematics education in the digital age.